Sosialisasi Dampak Negatif Gadget Di SD Negeri 15 Kota Sorong Papua Barat Daya - Muzakkir Pangri; Asih Ahistasari; Muhammad Jundullah; Muhammad Yusuf; Muhammad Surahmanto (CV. Multi Kreasi Media, 2024)
Gadgets, as modern communication tools, are making interactions between people easier. Nowadays, the development in communication has progressed rapidly with the presence of smartphones such as iPhone, Android, Blackberry, and notebook. However, in the context of early childhood developmental psychology (0-6 years), the use of gadgets can affect their social aspects. Gadgets can have both positive and negative effects on children's social and emotional development. Excessive use of gadgets can have adverse effects, such as making children more introverted, experiencing sleep disturbances, preferring to be alone, exhibiting aggressive behaviour, decreased creativity, and increased risk of cyberbullying. To overcome these negative impacts, some solutions that can be implemented include limiting the time of gadget use, parental supervision when children play gadgets, and setting an appropriate schedule so that gadget use does not interfere with early childhood social development. With this approach, it is hoped that the negative impact of gadget use can be minimised and children's social development maintained.